Factors Affecting Nutritional Status among Children Aged 12–23 Months - Tisnasari Hafsah; Lina Shabrina Qorib Sudaryo; Yovi Yoanita (Althea Medical Journal, 2019)
Background: In Indonesia about 18% of children, mostly in the first two years of life, are malnourished, causing a serious impact. Many factors are thought to affect nutritional status among young children. This study was conducted to determine factors affecting the nutritional status of children aged 12–23 months in West Java, Indonesia.Methods: This cross-sectional study used secondary data obtained from a Basic Health Research (Riset Kesehatan Dasar, RISKESDAS) 2010, conducted by Badan Penelitian dan Pengembangan Kesehatan (BALITBANGKES) Ministry of Health Republic of Indonesia. All of the data among children aged 12–23 months in West Java province was obtained. Statistical relationships between predisposing factors and nutritional status i.e. weight for height were analyzed using the chi-square test.Results: In total, 730 data were obtained, of which 567 data met the inclusion criteria. Malnutrition was detected in 101 (17.8%) children. There was a significant relationship (p=0.017, OR=2.6, 95% CI 1.1–5.8) between low birth weight and nutritional status. Nevertheless, no significant relationship was found between nutritional status and history of exclusive breastfeeding (p=0.629), complimentary feeding (p=0.949), vitamin A (p=0.209), infectious diseases (p=0.266), complete immunization status (p=0.420), and mother education level (p=0.251).Conclusions: The low birth weight is the only significant factor associated with the nutritional status among children less than 2 years old; resulting in that low birth weight had a 2.6 higher chance of malnutrition in the early years. Other factors are unexpectedly not significant in this study. There is thus a need to improve the quality of programs, focusing on childbearing mothers, during antenatal control.